O treino funcional aplicado à qualidade de movimento nos jogadores sub-19 do Leixões Sport Clube - Relatório de estágio profissionalizante na equipa Juniores A do Leixões Sport Club - Futebol, SAD - Álvaro Manuel Martins Valente da Silva Alves (2016)
Football is characterized for being a sport with an intermittent effort in which the capacity of making high intensity displacements in a repeated mode is decisive. Injury prevention is crucial, so that the athletes must have a good quality of their movement, which is, good mobility and stability. The aim of this work is based on the application of a functional training program aimed in the quality of movement of the players. In order to achieve this purpose, a professional internship was made at the A juniors' team (under-19) of Leixões Sport Club, where we effect two evaluations to 28 athletes, who were later divided into control and experimental group. The study sought to develop an intervention in the experimental group in typical limitations of football players, in order to improve their mobility and stability, as well as their muscular flexibility. The results showed improvements that are statistically significant of the experimental group regarding the action of the trunk in the single-leg squat and in the performance of the modified stand and reach test. In a general manner, the athletes presented better levels of flexibility, in comparison to their levels of mobility and stability. These should be subject of a greater attention by the coaches, in order to prevent injuries and to improve the performance of their players, by fighting compensatory changes in the movement of the athletes, which come from bad levels of mobility and stability of their articulations.